Por um reencontro com a natureza : contribuições da obra “O Homem e a Terra” de Élisée Reclus (1830-1905) para uma educação geográfica na atualidade - Silva, Carlos Henrique Amorim da (2022)
The present study is part of what Nature is currently seen primarily from the utilitarian perspective. that there is a view of domination over Nature and that it was also developed in several areas of science, including Geography. However, there is a perspective of perception. We can find such proposals in the proposals presented by the French anarchist ge Élisée Reclus (1830-1905). Reclus wrote several works, L'Homme et la Terre (1905-1908) being the main one, published posthumously. In it, the geographer expresses his social, historical, political and geographical thought in an independent and synthesized way. The work brings together a series of education, however, the present research focused on Reclus' affinities with education and teaching. Therefore, what we propose here is an epistemological reflection as a way of contributing to the debate on Geographic Education today. This study can deepen investigations on the subject, in addition to offering other ways of thinking about the investigation of Nature. To support this reflection, a Philosophical Hermeneutics was used in order to reflect in the present an idea proposed by Relus in his work, at the beginning of the 20th century. With the intuition of bringing this debate to the present, critically analyze the nuances of reformulation of High School, Law n. 13,415 of 02/16/2017. This new policy in the Brazilian basic education curriculum, also called “In high school this practice” shows a certain favoring of technical and teaching properties, giving a practical character to learning. Due to its immediacy nature, issues such as aesthetic perception and the notion of perception in relation to nature tend to be little explored. From this premise, we sought to develop a reflection around Reclus' thinking, thus establishing a bridge between the past and the possibilities of the present. The results show that Geographic Education can also be interpreted through a historical spiral. Reclus praised the teaching-learning methods that make up this creation, including: aesthetics, field classes, artistic activities and multidisciplinary dialogue.